Techno-economic Analysis of Rotor Flettner in Container Ship 4000DWT - Agoes Santoso; Muhammad Badrus Zaman; Arrijal Yudha Prawira (International Journal of Marine Engineering Innovation and Research, 2017)
Rotor flettner is a kind of technology which developed and used in 21st century. This technology is very simple, cylindrical in shape, applied in the upper deck, and rotated by the electrical motor. This technology uses wind energy and applicating magnus effect to create propulsion force. Rotor flettner depends on the condition of the sea wind. The designer has to check the weather condition in its route before make a design of rotor flettner. This kind of technology is not only useful for the economic side, but also, for the environment. Rotor flettner can reduce the emission of a ship. It helps to gain some power to increase in fuel saving.The emission can be decreased by the increasing of fuel saving. So, this technology is a kind of environmentally friendly technology that can be used for the future innovation.